Prevalence of Intestinal parasitic infections in HIV infected patients presenting with diarrhea and their association with CD4+ Counts - Singh, Desh D; Singh, Vinod (International Journal of Applied Sciences and Biotechnology, 2015)
Introduction: Intestinal parasitic infection has been an important problem in HIV patients, worldwide. Hence, this study was undertaken toestablish the prevalence of intestinal parasitic infection among people with and without HIV infection and its association with diarrhea andCD4 T-cell count. we aimed to measure the prevalence and identify the factors associated with intestinal parasitic infection in peopleinfected with HIV. Methodology: An analytical cross-sectional study in 1490 HIV-infected people attending for CD4 T-cell count wasconducted. Results: The incidence of intestinal parasitic infection was 22.4% (95% CI 29.25 to 38.25). In univariate investigation, age, sex,longer time because diagnosis of HIV, CD4 T-cell count of <200/μL, diarrhoea, wedded status, and individual under tuberculosis (TB)treatment were drastically related with increased chances of intestinal parasite infection. Nevertheless, in the logistic malfunctionrepresentation, only the CD4 T-cell count of <200/μL (accustomed OR=6.3, 95% CI 3.75 to 10.5), diarrhoea (accustomed OR=4.2,95% CI 2.7 to 6.45) and individual under TB cure (adjusted OR=4.35, 95% CI 2.7 to 6.45) remain as significant predictors. Onstratification, CD4 T-cell count of <200/ μL was independently associated with higher odds of protozoal as well as helminthes infection. Theparasites Cryptosporidium and Cyclospora were observed only in participants with CD4 T-cell counts <200/μL. Conclusions: HIV infectionincreased the risk of having intestinal parasites and diarrhoea. Therefore, raising HIV positive’s immune status and screening for intestinalparasites is important. This study showed that Immunodeficiency increased the risk of having opportunistic parasites and diarrhea. Therefore;raising patient immune status and screening at least for those treatable parasites is important. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12203 Int J Appl Sci Biotechnol, Vol. 3(1): 96-100